2(3b+4)-(b-5)=

Simple and best practice solution for 2(3b+4)-(b-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3b+4)-(b-5)= equation:


Simplifying
2(3b + 4) + -1(b + -5) = 0

Reorder the terms:
2(4 + 3b) + -1(b + -5) = 0
(4 * 2 + 3b * 2) + -1(b + -5) = 0
(8 + 6b) + -1(b + -5) = 0

Reorder the terms:
8 + 6b + -1(-5 + b) = 0
8 + 6b + (-5 * -1 + b * -1) = 0
8 + 6b + (5 + -1b) = 0

Reorder the terms:
8 + 5 + 6b + -1b = 0

Combine like terms: 8 + 5 = 13
13 + 6b + -1b = 0

Combine like terms: 6b + -1b = 5b
13 + 5b = 0

Solving
13 + 5b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + 5b = 0 + -13

Combine like terms: 13 + -13 = 0
0 + 5b = 0 + -13
5b = 0 + -13

Combine like terms: 0 + -13 = -13
5b = -13

Divide each side by '5'.
b = -2.6

Simplifying
b = -2.6

See similar equations:

| x+15=2x | | 5t-4s-3(2t-3s)= | | 36-5x+3= | | (15m-9m)-73=13 | | x+5y=10 | | -(5y+4)-(-4y-7)=-2 | | 146=-7x-5x+2 | | 3(r+1)-(2(3-2r)-3(3-r))=2(r+5)-4 | | 5s+10t=39 | | W^2+9=6w | | 9x-35=2x | | 53=6x-2x+9 | | s=2pirh | | -15=-13+x | | 3x^2+24x+36=0 | | 4z+8=12 | | 2x+2y=9 | | 12x^2-18x=0 | | 12.6=x-7.5 | | 4x^2+16x+12=0 | | -4(2-9n)= | | 7x+8=10x-1 | | 18-2x=5(x-2)-3x | | .5x-35=3x | | 7x-1=8x | | 10x+8y+5+19x-9y-2= | | 5r^2=9r | | 4x+30=7x | | 7x+9+9x-1=fd | | 10=-8-6 | | -lb-4l+1=10 | | x+14=-7 |

Equations solver categories